Likeability and Expert Persuasion: Dislikeability Reduces the Perceived Persuasiveness of Expert Evidence - Younan, Mariam; Martire, Kristy A. (Frontiers in Psychology, 2021)
With the use of expert evidence increasing in civil and criminal trials, there is concern jurors’ decisions are affected by factors that are irrelevant to the quality of the expert opinion. Past research suggests that the likeability of an expert significantly affects juror attributions of credibility and merit. However, we know little about the effects of expert likeability when detailed information about expertise is provided. Two studies examined the effect of an expert’s likeability on the persuasiveness judgments and sentencing decisions of 456 jury-eligible respondents. Participants viewed and/or read an expert’s testimony (lower vs. higher quality) before rating expert persuasiveness (via credibility, value, and weight), and making a sentencing decision in a Capitol murder case (death penalty vs. life in prison). Lower quality evidence was significantly less persuasive than higher quality evidence. Less likeable experts were also significantly less persuasive than either neutral or more likeable experts. This ‘penalty’ for less likeable experts was observed irrespective of evidence quality. However, only perceptions of the foundational validity of the expert’s discipline, the expert’s trustworthiness and the clarity and conservativeness of the expert opinion significantly predicted sentencing decisions. Thus, the present study demonstrates that while likeability does influence persuasiveness, it does not necessarily affect sentencing outcomes.